Holding a mirror up to Academic Development through the HELTASA (un)conferencing methodology - Williams, Sandra; Adams, Anthea; Geduld-Van Wyk, Charlene; Muhuro, Patricia (Critical Studies in Teaching and Learning, 2024)
We, Academic Development (AD) practitioners, question whether AD's objective in South Africa (SA) as a 'liberatory educational and social movement' to enhance educational quality for all students, is effectively pursued. AD practitioners often work on the fringes of the academy, fighting for relevance and legitimacy within an increasingly performative and managerialist academic culture. Despite innovative AD initiatives AD work is criticised for being unresponsive, unreflexive, conformist, and lacking theoretical, scholarly, and critical engagement. We use critical pedagogical praxis, particularly the constructs of critique, reflexivity, power, and self-reflection, to interrogate the continuous tension between AD intention and practice. Through (un)conference methodology, this auto-ethnographic account of individual and collective engagements, using the "holding the mirror up" metaphor, critically questioned the tension and misalignments between the AD mandate and practices. Although in a SA higher education context, this research could be beneficial to HE contexts globally, given the ubiquity of AD work.